T- MEC- UMSCA: saldos, a dos años de vigencia - Vázquez Ruiz, Miguel Ángel (Posgrados de la División de Ciencias Económica Administrativas, 2022)
The proximity between Mexico and the United States generates synergies in favor of an integration process that advances fueled by two types of forces: some are generated in the market by companies, economic actors, institutions and social organizations, and others are created deliberately by state apparatuses through the signing of agreements and treaties, such as the North American Free Trade Agreement (NAFTA), which evolved into the Mexico, United States, Canada Agreement (T-MEC). Together they add up to 28 years of formalized economic integration (26 of the first and two of the second). In this environment, the objective of this article is to analyze the balances shown for Mexico during the two years of validity of the T-MEC. Two results standout from the analysis: on the one hand, the trends of “trade creation” and investment are maintained, and on the other, this treaty covers issues of therelationship with North America that were not contemplated in NAFTA, such as changes in the rules of origin, the direct domain over Mexico’s hydrocarbons, agriculture, the environment, small and medium-sized enterprises and labor relations, among other issues that make the plot of asymmetrical interdependence relations between the two countries more complex.The methodology is documentary, descriptive and analytical and its main input was the content of the T-MEC chapters, highlighting the study of thosechapters that have the greatest impact on relations between Mexico and the United States.